Cervical nodal metastasis after malignant conversion of sinonasal inverted papilloma: Report of a rare case and literature review. (March 2019) - Sharbel, Daniel; Chat, Vipawee; Blumenthal, Daniel; Biddinger, Paul; Byrd, J. Kenneth
Abstract: Malignant conversion of sinonasal inverted papilloma (SNIP) occurs in approximately ten percent of cases. These tumors are classically described as locally destructive, but without metastatic potential. Only four cases of malignant conversion with cervical nodal metastases have been described in the English literature. We present the rare case of a 61-year-old Caucasian male with a nasopharyngeal recurrence of malignant SNIP with cervical and retropharyngeal nodal metastases. The patient underwent endoscopic transpterygoid with nasoseptal flap reconstruction, followed by staged bilateral and retropharyngeal node dissection. Histopathology of the specimens demonstrated poorly differentiated invasive nonkeratinizing squamous cell carcinoma with inverted-type features. Three months after surgery, the patient suffered from C1-C2 fractures consistent with osteoradionecrosis and expired. Although the rate of malignant conversion of SNIP is low, this case highlights the need for aggressive, definitive treatment and surveillance.